BARUDAK CERDAS DAN AKTIF : SOLUSI PENANGANAN ANAK PUTUS SEKOLAH DI DESA SIRNAGALIH KABUPATEN CIANJUR - Berliannanda, Anugrah Fitria; Kurniawan, Pratomo Cahyo (ABDI MAKARTI, 2024)
This community service activity was carried out with the main background so that the people of Sirnagalih village, Cianjur district, could massively reduce the school dropout rate with the Smart and Active Barudak program. Thus, this service activity aims to increase parents' awareness and children's interest in going to school. The service method is carried out by providing counseling and providing training in collaboration with the community work team in Sirnagalih village. In general, the activity went well. The participation and enthusiasm of the participants in this activity could be seen from the active discussions. The impact of this activity can increase parental awareness and children's interest in going to school so that the school dropout rate can be reduced and decrease drastically.